Mutation Detection in Tumor-Derived Cell Free DNA Anticipates Progression in a Patient With Metastatic Colorectal Cancer - de Figueiredo Barros, Bruna D.; Kupper, Bruna E. C.; Aguiar Junior, Samuel; de Mello, Celso A. L.; Begnami, Maria D.; Chojniak, Rubens; de Souza, Sandro J.; Torrezan, Giovana T.; Carraro, Dirce M. (Frontiers in Oncology, 2018)
Backgroung: The observation of tumor-derived cell-free DNA (ctDNA) in plasma brought new expectations to monitor treatment response in cancer patients. Case presentation: In an exploratory case of a 57 year-old male diagnosed with metastatic sigmoid adenocarcinoma, we used a hotspot panel with genes frequently mutated in cancer to identify tumor-specific mutations in primary tumor and metastasis. Results: Five different mutations were detected (KRAS, p.Gly12Val; TP53, p.Arg175His; RB1, p.Ile680Thr; ALK, p.Gly1184Glu; ERBB2, and p.Lys860Lys), three of them, detected in both tissues. All mutations were monitored in ctDNA in six plasma samples. Only KRAS and TP53 mutations were detected in the first plasma sample in high frequency. After one month of chemotherapy treatment the allele frequency of both mutations decreased below the limit of detection. Nevertheless, from the third month after the systemic treatment, the allele frequency of both mutations were detectable in plasma displaying a continually increase in the subsequent plasma samples. The remaining three mutations were not detected in any plasma samples collected. The disease progression detected by ctDNA anticipated the computed tomography measurements, which classified the metastatic lesions as stable throughout the treatment. Conclusions: Altogether, using liquid biopsy we were able to assess tumor heterogeneity and predict tumor progression, demonstrating the potential of ctDNA analysis as a sensitive and specific tool for monitoring patient’s response and prior identification of resistance to treatment.